서울의 초미세먼지 농도 추이 - 여민주(Min Ju Yeo); 임윤석(Yun Seok Im); 유승성(Seung Sung Yoo); 전은미(Eun Mi Jeon); 김용표(Yong Pyo Kim) (한국대기환경학회지(국문), 2019)
Public's anxiety on ambient PM2.5 level is increasing. To check whether the anxiety is related the PM2.5 concentration, the long-trem trends of (1) the PM2.5 concentration, high PM2.5 concentration frequency fraction, frequency of the high concentration occurrence duration time (three indicators), (2) PM2.5/PM10, (3) PM2.5/PM10 when PM2.5≥50 μg/m3 and <10 μg/m3 in Seoul between 2003 and 2018 are studied. Generally, all three indicators have decreased. For example, the annual mean PM2.5 concentration decreased from 37 μg/m3 in 2003 to 23 μg/m3 in 2018 in Seoul. However, the frequency fraction of PM2.5 exceeding 75 μg/m3 has increased since 2016. The frequency of the occurrence duration time of PM2.5≥50 μg/m3 has increased also since 2015. The PM2.5/PM10 increased while the concetnrations of PMs, because the PM10 concentration decreased more than PM2.5 concentration in Seoul between 2003 and 2018. The PM2.5/PM10 when PM2.5≥50 μg/m3 and <10 μg/m3 are also increased in Seoul between 2003 and 2018 and has incrased rapidly since 2014 when PM2.5≥50 μg/m3. KCI Citation Count: 0